Case Report: Multidrug Resistant Raoultella ornithinolytica in a Septicemic Calf - Pas, Mathilde L.; Vanneste, Kevin; Bokma, Jade; Van Driessche, Laura; De Keersmaecker, Sigrid C. J.; Roosens, Nancy H.; Haesebrouck, Freddy; Boyen, Filip; Pardon, Bart (Frontiers in Veterinary Science, 2021)
Sepsis is a frequent life-threatening condition in young calves, requiring rapid broad spectrum and bactericidal therapy to maximize survival chances. Few studies have identified and characterized bacteria involved in sepsis in calves. This report demonstrates the involvement of a multidrug resistant Raoultella ornithinolytica, an emerging pathogen in human medicine, in a calf with suspected sepsis. R. ornithinolytica was identified by MALDI-TOF MS from blood cultures of a critically ill calf. Susceptibility testing showed phenotypic resistance against ampicillin, gentamicin, potentiated sulphonamides, streptomycin, tetracyclines and intermediate susceptibility for enrofloxacin. Whole genome sequencing confirmed identification as R. ornithinolytica and the multidrug resistant character of the isolate. Antimicrobial resistance genes acting against aminoglycosides, beta-lactam antibiotics, fosfomycin, quinolones, sulphonamides, trimethoprim and tetracyclines were found. The calf recovered after empirical parenteral therapy with enrofloxacin and sodium penicillin for seven days. Ancillary therapy consisted of fluid therapy, ketoprofen and doxapram hydrochloride. To the authors’ knowledge, this is the first report characterizing a multidrug resistant R. ornithinolytica isolate from blood culture in cattle. It is currently unknown whether animals and farms may act as reservoirs for multidrug resistant R. ornithinolytica strains.